Foraging sequence, energy intake and torpor: an individual‐based field study of energy balancing in desert golden spiny mice - Ofir Levy; Tamar Dayan; Shay Rotics; Noga Kronfeld‐Schor (Ecology Letters, 2012)
We studied the relationship between sequence of foraging, energy acquired and use of torpor as an energy‐balancing strategy in diurnally active desert golden spiny mice. We hypothesised that individuals that arrive earlier to forage will get higher returns and consequently spend less time torpid. If that is the case, then early foragers can be viewed as more successful; if the same individuals arrive repeatedly early, they are likely to have higher fitness under conditions of resource limitation. For the first time, we show a relationship between foraging sequence and amount of resources removed, with individuals that arrive later to a foraging patch tending to receive lower energetic returns and to spend more time torpid. Torpor bears not only benefits but also significant costs, so these individuals pay a price both in lower energy intake and in extended periods of torpor, in what may well be a positive feedback loop.